Prediction of the surface temperature of building-integrated photovoltaics: development of a high accuracy correlation using computational fluid dynamics - Zhang, Ruijun; Mirzaei, Parham A.; Carmeliet, Jan (Elsevier, 2017)
Building-integrated photovoltaic (BIPV) panels are generally expected to operate for over 25 years to be viewed as an economically viable technology. Overheating is known to be one of the major deficiencies in reaching the targeted lifespan goals. Alongside the thermal degradation, the operational efficiency of the silicon-based solar panel drops when the surface temperature exceeds certain thresholds close to 25 °C. Wind-driven cooling, therefore, is widely recommended to decrease the surface temperature of PV panels using cavity cooling through their rear surfaces. Wind-driven flow can predominantly contribute to cavity cooling if a suitable design for the installation of the BIPV systems is considered.